Menemukan Strategi Pengembangan Kawasan Industri Melalui Analisis Sektor Unggulan Kota Binjai - Dessy Eresina Pinem (Department of Urban and Regional Planning, Diponegoro University, 2016)
Manufacturing industry is a leading sector that has potentials for promoting rapid growth in a region. The growth that relies on the industrial sector is driven by the sales of production, employment, and other multiplier effects so that many districts or cities in North Sumatra are eager to developing this sector. The types of industry that can be developed are supposed to be appropriate to the industry potentials and local resources in order to boost an optimal growth in the region. In the spatial planning (RTRW) of Binjai City 2011 - 2030, the North Binjai District designated as an industrial area. The type of industry which is planned to be developed is a high-tech industry. However, the problem is whether the type specified in the RTRW is suitable to the potentials of local resources? This paper aims to find out the suitable industry to be developed in compliance with the local potentials, especially in the North Binjai District. The analyses applied are LQ, shift share and SWOT to discover the potentials and advantages of the city in comparison to those industries endorsed in the RTRW. The results show that the industrial sector is neither the leading nor potential sector in Binjai. Meanwhile, the results of LQ and shift share analyses show that the sector with the potentials to be developed in Binjai is the construction sector, finance, and services. The similarity to the RTRW policy is only in the service sector. It shows that the service sector can be developed while the computer industry, multimedia, publishing, and printing mismatch the local potentials. However, if the government still wants to develop the industrial sector in North Binjai, there should be diversification strategies to promoting the leading sectors such as building materials and mining industries.